Dental root agenesis following radiation and antineoplastic therapy: A Case Report - Abdul Hafiz; Abdulla Mufeed; Punit Bharadwaj; Dinesh Rao (Wolters Kluwer Medknow Publications, 2016)
The survival rates of patients suffering from various childhood neoplasms have improved dramatically with the advent of chemo-radiation therapy. The harmful effects of chemo-radiation therapy in the oro-facial region such as root agenesis, short roots, impaired amelogenesis, dentinogenesis, radiation caries, and other soft tissue pathologies are well recognized. In spite of these documented risks, the antineoplastic treatment modalities continue to serve the patient for overall improvement in survival and quality of life. However, a thorough understanding of the growth and development process and its relation with the complex antineoplastic treatment is very important for all clinicians. Such awareness could significantly improve the status of patients in the posttreatment period with the implementation of proper preventive and interceptive measures. This article intends to document a case of root agenesis that developed secondary to chemo-radiation therapy in a 12-year-old girl.